Innovative Antifungal strategies: Terbinafine hydrochloride in Niosomal carriers - Shraddha Bandgar; Raju Rathod; Vivekanand Teli; Pankaj Jadhav (International Journal of Fungi, 2025)
Onychomycosis, an infection caused by fungi that affects fingernails or toenails, causes the nails to grow, separate from the nail bed, and become discoloured. While anybody can get, those with weakened immune systems, children and the elderly are especially susceptible. Present study was related to formulate an effective nail lacquer that would treat onychomycosis by utilizing Terbinafine hydrochloride. In this study, niosomes of a medication called terbinafine hydrochloride, an antifungal drug, were mixed in Nitrocellulose or Eudragit RL 100, a well-known polymer. Nail lacquer is created by simple mixing procedure. The frequency of application was reduced for twice per week by utilizing polymers like nitro cellulose, to maintain the release of drug for a whole day. Infection is characterized by discomfort as well as swelling surrounding the nail, as well as an unpleasant smell. Therefore, ethyl acetate will help to disguise the disagreeable smell and also have an anti-inflammatory effect to improve patient acceptability and compliance. Oleic acid serves as a penetration enhancer, boosting the medicament's capacity to enter into the nail bed. When improving the formulation, factors including water resistance testing, drying time and non-volatile content were taken into account. For the optimized formulation, the optimal drying time was 2 minutes. Consequently, niosomal nail lacquer containing Terbinafine hydrochloride was successfully produced.
Keywords: Niosomal nails lacquer; Nitro cellulose; Onychomycosis; Terbinafine hydrochloride; hyperkeratosis